High Uses of Emergency Care and High Prevalence of Medication Adverse Effects in Gastroparesis Patients at a Tertiary Academic Center: Cross Sectional Survey. Issue 3 (September 2022) - Heckroth, Matthew; Tansel, Aylin; Mathur, Prateek; Stocker, Abigail; Cutts, Teresa; Abell, Thomas L.
Introduction: Gastroparesis (Gp) syndromes are associated with high healthcare burden with high rates of emergency and inpatient utilization. Urgent care rates for Gp remain unknown. In acute care settings, medications are often used to assuage symptoms. Unfortunately, real-world medication use and adverse effects is lacking. We aimed to assess acute care (urgent care, emergency, inpatient) utilization rates and predictors. As a secondary aim, we aimed to assess both exposure of and adverse effects associated with medications used for gastroparesis. Methods: Surveys were administered at a tertiary referral center, returned during that visit, or mailed back. Open-ended questions were used, whenever possible, to prevent response bias for patients to report the adverse effects they experienced. Results: 62 patients (93.5% women) completed the survey. Patients were most frequently exposed to metoclopramide (71.0%), ondansetron (83.9%), and promethazine (72.6%). Of prokinetics, metoclopramide had the highest prevalence of adverse effects (59.1%). The rates of Gp-related urgent care visits, emergency visits, and hospitalizations within 6 months were 19%, 47%, and 26%, respectively. Multivariable logistic regression analysis revealed that patients aged 45-64 were a significant predictor for Gp-related urgent care utilization (aOR 8.8 [95% CI 1.2-65.4, p 0.03]). Low income was a significant predictor for gastroparesis-related hospitalization (aOR 6.8 [95% CI 1.1-42.7, p 0.04]). Conclusion: This survey found high rates of emergency care usage and high prevalence of adverse effects in commonly used medications for Gp patients. Urgent care may be an underutilized tool to reduce emergency care usage in Gp. Treatment algorithms for gastroparesis patients built on balancing adverse effects compared with efficacy are needed. Additionally, early integration of safe complementary integrative Gp therapies may minimize patient exposure while preserving treatment efficacy.